1975
DOI: 10.1007/bf02532427
|View full text |Cite
|
Sign up to set email alerts
|

Substitution reactions of linoleic acid hydroperoxide isomerase

Abstract: Linoleic acid hydroperoxide isomerase was extracted from corn germ and partially purified by differential centrifugation. This enzyme catalyzed the isomerization of linoleic acid hydroperoxide.(see article) Isomerase also catalyzed the substitution of various reagents at the carbon bearing the hydroperoxide group. These fatty acid products had the following functional groupings: (see article) where X is either oleoyloxy, ethylthio, or methoxy resulting from the presence of oleic acid, ethanethiol, or methanol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

1975
1975
1996
1996

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…In addition to the usual products, a-and "y-ketols, substitution compounds resulted. One of these was the oleoyl ester of the c~-ketol, which was a reaction product described by Christianson and Gardner (7). In our study, another substitution compound was identified as the oleoyl ester of 3'ketol.…”
Section: Substitution Reaction With Oleic Acidsupporting
confidence: 69%
See 4 more Smart Citations
“…In addition to the usual products, a-and "y-ketols, substitution compounds resulted. One of these was the oleoyl ester of the c~-ketol, which was a reaction product described by Christianson and Gardner (7). In our study, another substitution compound was identified as the oleoyl ester of 3'ketol.…”
Section: Substitution Reaction With Oleic Acidsupporting
confidence: 69%
“…Substitution Products. Those products from substitution reactions with either oleic acid or methanol were isolated by silicic acid column chromatography by the methods of Christianson and Gardner (7). The substitution products described here were minor products compared to those described previously (7).…”
Section: Enzyme Reactionmentioning
confidence: 87%
See 3 more Smart Citations